The Effect of Additional Lemongrass Extract (Cymbopogon nardus L.) on the Characteristics of Edible Film Sodium Alginate and Arabic Gum - Jein Lisdayanti Liah; Lahming; Reski Febyanti Rauf (Formosa Journal of Science and Technology, 2023)
This research is a quantitative study that uses quasi-experimental research methods that aim to analyze the effect of adding lemongrass extract (Cymbopogon Nardus L.) to the characteristics of the edible film, and to analyze the antimicrobial activity of the edible film. This study used a completely randomized design (CRD) with the addition of lemongrass extract, namely control, 1%, 1.5%, 2.5%. And it was repeated 3 times so that 12 treatment units were obtained. The data obtained were calculated using Analysis of variance (ANOVA) and if there was a difference, continued with Duncan's test using SPSS 16. The results showed that the addition of 2.5% lemongrass extract affected the characteristics of the edible film form of thickness, water resistance, elongation, and has the ability to inhibit pathogenic bacteria with a concentration of 2.5%. However, there was no significant difference in the tensile strength with a concentration of 2.5%.